1997
DOI: 10.1002/hep.510250132
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone withdrawal late after adult liver transplantation reduces diabetes, hypertension, and hypercholesterolemia without causing graft loss

Abstract: plantation are due to cardiovascular disease and another 40% We prospectively withdrew prednisone in 28 adult paare due to infection. 4 tients who had stable graft function more than 2 yearsWe previously have observed a high prevalence of cardioafter orthotopic liver transplantation (OLTx) and had vascular risk factors in patients late after liver transplantabeen on 5 mg/d prednisone for at least 6 months. Prednition. 4 One year after successful liver transplantation in our sone was decreased from 5 mg/d to 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 15 publications
(2 reference statements)
3
63
2
Order By: Relevance
“…9 The fact that immunologic graft loss is rare after liver transplantation, combined with the severe side effects of long-term prednisone therapy, supports steroid withdrawal in liver transplant recipients. 8,10 In our series, as in other groups, steroid withdrawal was achieved earlier and in more patients receiving tacrolimus than cyclosporine therapy. 11,12 However, other studies showed no difference in steroid withdrawal between tacrolimus-and cyclosporine-treated patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…9 The fact that immunologic graft loss is rare after liver transplantation, combined with the severe side effects of long-term prednisone therapy, supports steroid withdrawal in liver transplant recipients. 8,10 In our series, as in other groups, steroid withdrawal was achieved earlier and in more patients receiving tacrolimus than cyclosporine therapy. 11,12 However, other studies showed no difference in steroid withdrawal between tacrolimus-and cyclosporine-treated patients.…”
Section: Discussionsupporting
confidence: 75%
“…8 The majority of studies of steroid withdrawal after liver transplantation have been conducted in pediatric transplant recipients. 9 The fact that immunologic graft loss is rare after liver transplantation, combined with the severe side effects of long-term prednisone therapy, supports steroid withdrawal in liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Options include reduction in corticosteroids, 17 substituting tacrolimus for cyclosporine, 18 reducing CNI doses by adding mycophenolate mofetil (MMF), 19 or converting to sirolimus-based immunosuppression. 20 These decisions should be made with the transplant hepatologist involved.…”
Section: Hypertensionmentioning
confidence: 99%
“…6 from the University of California Los Angeles reported in 1995 that only 2 of 33 patients receiving cyclosporine therapy who underwent steroid withdrawal experienced biopsy-proven rejection. At the University of Colorado, Stegall et al 7 prospectively withdrew prednisone in 28 adult OLT patients. Two patients experienced biopsy-proven rejection and 2 others experienced elevation of liver tests but were not biopsied.…”
Section: Commentsmentioning
confidence: 99%